2021
DOI: 10.1186/s12885-021-08156-1
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab with or without enzalutamide in selected populations of men with previously untreated metastatic castration-resistant prostate cancer harbouring programmed cell death ligand-1 staining: a retrospective study

Abstract: Background The purpose of this retrospective study was to evaluate the survival outcomes of pembrolizumab (PEM) plus enzalutamide (ENZ) versus PEM alone in selected populations of men with previously untreated metastatic castration-resistant prostate cancer (mCRPC) harbouring programmed cell death ligand-1 (PD-L1) staining. Methods Consecutive men with previously untreated mCRPC harbouring PD-L1 staining who underwent treatment with PEM plus ENZ (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…In addition, various PD-L1 antibody clones were rarely simultaneously tested on the same series. Considering the heterogenous or focal expression of PD-L1 by PC cells (Figure 2), the use of TMA reduced the number of evaluable cells, probably causing false-negative results in some cases; conversely, some trials included only PD-L1+ cases, causing a selection bias for the abovementioned positivity rates [154].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, various PD-L1 antibody clones were rarely simultaneously tested on the same series. Considering the heterogenous or focal expression of PD-L1 by PC cells (Figure 2), the use of TMA reduced the number of evaluable cells, probably causing false-negative results in some cases; conversely, some trials included only PD-L1+ cases, causing a selection bias for the abovementioned positivity rates [154].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of our review, the positivity rate of different PD-L1 antibody clones in tumor cells ranged from 3% (SP142) to 50% (ABM4E54), excluding the single case tested for RM-320. The positivity rate of clone 22C3 (the most used to assess eligibility for administration of pembrolizumab) was 11% after excluding cases with a CPS score of ≥1 (as it was unclear if tumor cells resulted positive), 41% after including those cases, and 78% only considering the cases scored as CPS ≥1 [9,12,13,21,27,32,35,51,77,80,83,90,154].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome 9p gains are common DNA copy number aberrations, significantly associated with advanced tumor stage and regional lymph node metastases in sporadic PCs [157,158]. Budczies et al identified a 7.8-Mbp region of 38 genes located in chromosome 9p24, including genes regulating cell cycle and immune-response in PC (such as PD-L1, PD-L2 and JAK2).…”
Section: Data From the Cancer Genome Atlas (Tcga) Analysismentioning
confidence: 99%
“…Despite the cytoplasmatic protein tail lacks the canonical motifs for signal transduction, PD-L1 reverse intracellular signaling has been recently demonstrated in immune cells, lymphomas and solid tumors. Some non-canonical signaling transduction motifs have been identified in the intracellular tail, being involved in cancer cell proliferation and survival, inhibition of autophagy, mTOR activation, and IFN-β toxicity [158,184].…”
Section: Intratumoral Lymphocytesmentioning
confidence: 99%